International security in practice : the politics of NATO-Russia diplomacy - Pouliot, Vincent, 1979- (Cambridge studies in international relations, 2010)
"How do once bitter enemies move beyond entrenched rivalry at the diplomatic level? In one of the first attempts to apply practice theory to the study of International Relations, Vincent Pouliot builds on Pierre Bourdieu's sociology to devise a theory of practice of security communities and applies it to post-Cold War security relations between NATO and Russia. Based on dozens of interviews and a thorough analysis of recent history, Pouliot demonstrates that diplomacy has become a normal, though not a self-evident, practice between the two former enemies. He argues that this limited pacification is due to the intense symbolic power struggles that have plagued the relationship ever since NATO began its process of enlargement at the geographical and functional levels. So long as Russia and NATO do not cast each other in the roles that they actually play together, security community development is bound to remain limited"--Provided by publisher